MENTAL FORAMEN, INFERIOR ALVEOLAR CANAL AND MORPHOLOGY OF MAXILLARY SINUS: A REVIEW - SHAILA ZAMAN; MOHAMMAD KHURSHEED ALAM; HAMID H ENEZEI; REHANA BASRI; SHAIFULIZAN ABDUL RAHMAN (International Journal of Pharma and Bio Sciences, 2015)
The aim of this study was to review the different locations of mental foramen, inferior alveolar canal and morphology of maxillary sinus in between different ages in different population. Several electronic databases such as Google Scholar, PubMed, Web of Science and Science Direct were systematically searched for studies published until March 2015. The locations of mental foramen and inferior alveolar canal have many variations. These variations are influenced by races and sometimes gender.